Interspecific and intraspecific variation in Coffea sp. using fruit metric and landmark-based geomorphometric analyses - Sanchez, Joana Camille S.; Quilang, Jonas P.; Mojica, Ruel M.; Cao, Ernelea P. (2018)
Coffee is considered one of the most popular cash crops in the world. In the Philippines, three species of Coffea and correspondingly four varieties (C. arabica var. Red Bourbon, C. canephora var. Robusta, C. liberica var. Liberica, and C. liberica var. Dewevrei) are grown to produce coffee with each having a distinct taste and aroma. However, misidentification of farmers based on morphological traits is often a problem. In this study, an easy, fast, and inexpensive method for differentiating the four different varieties of Coffea was established using metric and geomorphometric analysis. At least 30 berries were collected for each variety from a single site at the Cavite State University in Indang, Cavite wherein metric characters were measured and analyzed using ANOVA, SIMPER, and ANOSIM. At the same time, geomorphometric analysis of the fruit shape – particularly the shape of the berry as oriented radially and longitudinally – was also done using CVAgen. For the metric analysis, the length of the minor radial axis was the most discriminating characteristic. In the geomorphometric analysis, the longitudinal view of C. arabica var. Red Bourbon, C. canephora var. Robusta, and C. liberica var. Liberica was found to differentiate them from each other. Contrastingly, C. liberica var. Dewevrei was the only variety that could not be distinguished in any geomorphometric analyses and can only be distinguished using metric analysis.
Keywords: Coffee